2005
DOI: 10.1002/ejoc.200400614
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Absolute Configuration of Inherently Chiral Resorc[4]arenes

Abstract: The absolute configuration of twelve inherently chiral resorc‐arenes was determined using a combination of the X‐ray structure of (–)‐3a and optical rotation as well as NMR techniques. Starting from a racemic mixture of 1 both diastereomers (–)‐3a and (+)‐3b can be obtained in high yields in two steps and the absolute configuration of these diastereomers could be determined by X‐ray analysis. Using enantiomerically pure (–)‐1 for the same reactions, however, (+)‐3b is formed. The alkylation of (–)‐1 with (S)‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The Loughborough group also prepared and used the racemic mixture of resorcin[4]arenes 7 in order to prepare tetracamphorsulfonates also with the use of ( S )‐(+)‐10‐camphorsulfonyl chloride. A very recent publication10 also used the absolute configurations that were reported earlier 9. The Bielefeld group repeated the experiments with an enantiomerically pure sample of compound 7 ,11 that involved the formation of a crystalline amide: those results confirmed the initial results of the Loughborough and Curtin groups.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…The Loughborough group also prepared and used the racemic mixture of resorcin[4]arenes 7 in order to prepare tetracamphorsulfonates also with the use of ( S )‐(+)‐10‐camphorsulfonyl chloride. A very recent publication10 also used the absolute configurations that were reported earlier 9. The Bielefeld group repeated the experiments with an enantiomerically pure sample of compound 7 ,11 that involved the formation of a crystalline amide: those results confirmed the initial results of the Loughborough and Curtin groups.…”
Section: Methodsmentioning
confidence: 67%
“…The absolute configurations of the enantiomeric tetraalkoxyresorcin[4]arenes could also be established by reference to the known absolute configurations of chiral nonracemic tetrabenzoxazines such as the compounds 5 and 6 , whose structures were known from X‐ray crystallographic data 6b. When the study, conducted at Loughborough and Curtin, including the determination of the absolute configurations of a number of camphorsulfonates derived from racemic tetraalkoxyresorcin[4]arenes and their hydrolysis products, was almost ready for publication, the absolute configurations of the tetramethoxyresorcinarenes 7 derived from 3‐methylbutanal and 3‐methoxyphenol were published 9. The Loughborough and Curtin groups were surprised that the results of their study were not in agreement with the published results, and the Loughborough group therefore repeated their experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The absolute stereochemistry of compound ( M , R , R )‐ 20a was established by single‐crystal X‐ray structure determination, shown in Figure 8 41. After this part of the study had been completed, the successful aminolysis of a compound related to 18 was reported in which the reaction of an esterwas heated with ( S )‐(–)‐(α‐methylbenzyl)amine at 160 °C 37b,42…”
Section: Resultsmentioning
confidence: 99%
“…The C-alkylresorcin [4]arenes are capable of forming solvates with the recrystallized solvent and several studies have reported the presence of these solvates [8,18,[22][23][24][25]. In the present work, the formation of solvates was avoided using vacuum techniques and high temperatures, as was mentioned in Section 2.1.…”
Section: Resultsmentioning
confidence: 84%